Development of Management Principles in Modern Conditions ("Journal "U". Economy. Management. Finance.", 2023)
The relevance of the topic is due to the fact that without effective management it is impossible to ensure the development of both an individual organization and the economy as a whole. The changes taking place in the modern market are gradually filling the principles of management with new content. As a result of the reaction to new phenomena occurring in the modern economy, the initial provisions on management require compliance with the new conditions of social development, the competent application of which will allow to properly coordinate the work of the organization, determine the necessary strategy, and therefore achieve the desired results.
Keywords: management; management principles; efficiency; development